Treatment of unfavourable results of flexor tendon surgery: Skin deficiencies - David Elliot; Thomas Giesen (Indian Journal of Plastic Surgery)
We recently reported a small study at the Federation of European Societies for Surgery of the hand, which was entitled ′What is secondary flexor tendon surgery′? This study concluded that ′secondary flexor tendon surgery′ was a generic name encompassing a multitude of pathologies. Between 10% and 15% of cases exhibited pathology of the skin and subcutaneous fat and required flap reconstruction of these tissues. Skin replacement may be used prophylactically at primary surgery or become necessary at secondary surgery after release of scar contractures, to achieve cover of vital structures. The long-term problem of skin deficiency relating to flexor tendon function is one of loss of extension from longitudinal scar shortening of the integument, even if the flexor tendons are primarily concerned with bending the digits, not straightening them. This loss of extension can only be tolerated in a hand to a certain degree without significant loss of function. This paper is largely an analysis of the flaps available and suitable for different degrees of skin deficiency and at different places along the course of the flexor system. It attempts to dispel the idea that ′any flap will do′ provided the flexors are adequately covered.